Antimicrobial Efficacy of 2.5% Sodium Hypochlorite, 2% Chlorhexidine, and 1.5% Hydrogen Peroxide on Enterococcus Faecalis in Pulpectomy of Necrotic Primary Teeth - Iman Parisay; Maryam Talebi; Shamimeh Asadi; Ali Sharif moghadam; Mohammad Hossein Nikbakht (Journal of dental materials and techniques, 2021)
Introduction: The success of the endodontic treatment is closely associated with eliminating endodontic microbiota especially bacteria like Enterococcus Faecalis (E. Faecalis). Irrigation solutions are suggested for this purpose but there are contraries regarding irrigations and their concentrations. This study aimed to compare antibacterial efficacy of irrigations including 2.5% Sodium hypochlorite (NaOCl), 2% Chlorhexidine (CHX), and 1.5% Hydrogen peroxide (H2O2).  Methods: Fifty deciduous human extracted teeth were divided into 3 groups of 15 teeth, 2.5% NaOCl, 2% CHX, 1.5% H2O2, and 5 teeth in the negative control group. Later, root canals were inoculated by E. Faecalis. After cleaning and shaping, we irrigated the root canals of the teeth in each group with NaOCl, CHX, and H2O2. Samples were obtained again and sent for microbiological evaluation. Wilcoxon signed-rank test, Paired sample T-test, and Kruskal–Wallis were used to analyze data. Results: All 3 groups showed significant bacterial reduction (p <0.05). NaOCl and CHX showed no significant difference (P=0.415). But the reduction of these 2 groups was higher than H2O2 (p Conclusions: 2.5% NaOCl and 2% Chlorhexidine showed considerable efficacy against E. Faecalis while 1.5% Hydrogen peroxide was not able to eradicate all of E. Faecalis colonies. Hence, NaOCl and CHX solutions can be used for decontamination of infected root canals